The Principle of Wisdom Among Tobacco Farmers - Mahmudi, Mahmudi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The term of local wisdom is the wisdom of local communities which is important to study considering that this is a moral message for us to overcome religious radicalism in the name of truth. In fact, if the truth of religion is actualized by the form of violence, it becomes anarchism. This research seeks to reveal the meaning of wisdom for the tobacco farming community in Daleman Ganding, Sumenep. The research subjects consisted of three people in the category who had been farmers for a long time and had the wisdom to live with the recognition of the community who lived together. The theory used in this research is the theory of wisdom which originates from philosophy as a way of life including: values, norms, ethics and beliefs of local communities. This research resulted in the conclusion that the Daleman Ganding Community has local wisdom principles that need to be disseminated in order to overcome religious radicalism.